2020
DOI: 10.18632/aging.102699
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive medications are associated with the risk of kidney and bladder cancer: a systematic review and meta-analysis

Abstract: Several studies have indicated that the use of antihypertensive medications may influence the incidence of bladder/kidney cancer, with some scholars refuting any such association. Hence, a systematic review is needed to verify this linkage. we comprehensively searched PubMed, Embase, Web of Science, and the Cochrane Library for original studies reporting a relationship between antihypertensive medications and risk of bladder/kidney cancer. We included 31 articles comprising 3,352,264 participants. We found a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 60 publications
1
37
1
Order By: Relevance
“…The study had several limitations. First, there was no data on anti‐hypertensive medication which have overall shown a positive association with BC 34 and might modify or mediate the association between BP and BC. Our results for BC‐specific mortality should be interpreted with caution, as these were rather inconsistent and based on small numbers, especially among never‐smokers.…”
Section: Discussionmentioning
confidence: 99%
“…The study had several limitations. First, there was no data on anti‐hypertensive medication which have overall shown a positive association with BC 34 and might modify or mediate the association between BP and BC. Our results for BC‐specific mortality should be interpreted with caution, as these were rather inconsistent and based on small numbers, especially among never‐smokers.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] The most recent evidence in this setting comes from a systematic review of 27 observational studies that found an association between diuretic use and the risk of kidney cancer (RR 1.34, 95% CI [1.19-1.51]) that increased with the duration of treatment and was still significant after adjusting for hypertension and smoking. 27…”
Section: Antihypertensive Drugs and Cancer Risk Diureticsmentioning
confidence: 99%
“…The latest meta-analysis and systematic review ( Xie et al, 2020 ) concluded that each class of anti-hypertensive drugs was associated with renal cancer (RR 1.45; 95% CI 1.20–1.75), while ARBs were associated with an increased risk of bladder cancer (RR 1.07; 95% CI 1.03–1.11). Although the conclusions were adjusted for factors, such as blood pressure and smoking, most of the included studies were observational and presented significant heterogeneity.…”
Section: The Association Between Anti-hypertensive Drugs and Cancer Rmentioning
confidence: 99%
“…Subsequently, many investigated the correlation of anti-hypertensive drugs and cancer. The researchers conducted many systematic reviews and meta-analyses regarding various perspectives, especially from the aspects of tumor types (Xie et al, 2020) and anti-hypertensive drug types (Zhao et al, 2016;Datzmann et al, 2019;Asgharzadeh et al, 2020b). Unfortunately, there was no clear answer to eliminate these anxieties; for example, Sipahi et al (Sipahi et al, 2010) showed angiotensin receptor blockers (ARBs) were moderately associated with cancer while Y.T.…”
Section: Introductionmentioning
confidence: 99%